Communism or communists? Soviet legacies and corruption in transition economies - Alexander Libman; Anastassia Obydenkova (Frankfurt School of Finance & Management, 2013)
This working paper contains supplementary material to the paper Communism or Communists? Soviet Legacies and Corruption in Transition Economies. The supplementary material covers the description of calculation and sources of key variables, as well as reports summary statistics and provides estimation tables and outcomes for robustness checks, used to validate the results described in the published paper.
Keywords: D73; K42; P26; 330; corruption; transition economies; path dependence; Soviet legacies